Multi‐stage flexible planning of regional electricity‐HCNG‐integrated energy system considering gas pipeline retrofit and expansion. Issue 15 (6th September 2022) - Qiu, Yue; Zhou, Suyang; Gu, Wei; Ding, Shixing; Han, Gaoyan; Zhang, Kang; Lv, Hongkun
Abstract: The development of hydrogen‐enriched compressed natural gas (HCNG) can make full use of the existing natural gas infrastructure, thereby alleviating the economic and technical pressure on the development of pure hydrogen. This paper proposes a multi‐stage flexible planning method for the regional electricity‐HCNG‐integrated energy system (E‐HCNG‐IES), which considers the medium and long‐term dynamic characteristics of the E‐HCNG‐IES. For each sub‐regional energy station, an energy‐hub type model including hydrogen/HCNG‐related equipment and facilities is established. Considering the influence of hydrogen blending on the energy delivery capacity and line pack of pipelines, a hydrogen‐resistant retrofit model for existing natural gas pipelines between sub‐regions is proposed. Meanwhile, the model for newly constructed hydrogen pipelines is also presented. Subsequently, a series of flexibility evaluation indicators are proposed to support the performance analysis of planning schemes. The lateral comparison of sub‐cases in Changzhou, China demonstrates that considering the hydrogen‐resistant retrofit of natural gas pipelines can reduce the construction cost of hydrogen pipelines by about 37.12%. The peak shaving capacity of underground hydrogen storage (UHS), the energy recycling ability of turbo expander (TE), and the space‐time decoupling ability of hydrogen in energy supply and demand have also been confirmed.